Plasma levels of MASP‐1, MASP‐3 and MAp44 in patients with type 2 diabetes: influence of glycaemic control, body composition and polymorphisms in the MASP1 gene. (20th April 2017) - Krogh, S. S.; Holt, C. B.; Steffensen, R.; Funck, K. L.; Høyem, P.; Laugesen, E.; Poulsen, P. L.; Thiel, S.; Hansen, T. K.
Summary: Mounting evidence indicates that adverse activation of the complement system plays a role in the development of diabetic vascular complications. Plasma levels of the complement proteins mannan‐binding lectin (MBL) and its associated serine proteases (MASP‐1 and MASP‐2) are elevated in diabetes. We hypothesized that single nucleotide polymorphisms (SNPs) in the MASP1 gene may contribute to altered plasma levels of the belonging gene products; MASP‐1, MASP‐3 and mannan‐binding lectin‐associated protein of 44 kDa (MAp44) in patients with type 2 diabetes. To investigate this, we compared plasma levels of MASP‐1, MASP‐3 and MAp44 in 100 patients with type 2 diabetes and 100 sex‐ and age‐matched controls. Ten carefully selected SNPs were analysed using TaqMan ® genotyping assay. Additionally, we included a streptozotocin‐induced diabetes mouse model to directly examine the effect of inducing diabetes on MASP‐1 levels. MASP‐1 levels were significantly higher among patients with type 2 diabetes compared with healthy controls ( P = 0·017). Five SNPs (rs874603, rs72549254, rs3774275, rs67143992, rs850312) in the MASP1 gene were associated with plasma levels of MASP‐1, MASP‐3 and MAp44. In the diabetes mouse model, diabetic mice had significantly higher MASP‐1 levels than control mice ( P = 0·003). In conclusion, MASP‐1 levels were higher among patients with type 2 diabetes and diabetic mice. The mechanism behind this increase remains elusive. Abstract : The plasma levels of the manan‐binding lectin (MBL) associated serine proteases (MASP‐1 and MASP‐3) and MBL‐associated protein of 44 kDa (MAp44) were examined in patients with type 2 diabetes and control subjects. MASP‐1 levels were significantly higher in the patients while the two other products of the same gene (MASP‐3 and MAp44) did not show any difference between patients and control groups. Elevated MASP‐1 concentrations were also found in a mouse model of diabetes.